PERANCANGAN MEDIA PEMBELAJARAN E-TEMBANG BERBASIS ANDROID UNTUK BERBAGI ILMU TEMBANG MACAPAT - Haryo Kusumo; dani sasmoko (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2019)
Abstract Along with the development of information technology, especially in the field of communication, the use of Android mobile phones has become commonplace. The tedious and monotonous learning process of Tembang Mocopat generates the students' disinterest in learning it at school. Regarding this, E-Tembang is used to increase students'interest at school and help to preserve the culture of Tembang macapat . This study used the R & D method to conduct the research and Android Studio to create the application and took 100 respondents for their opinions. The result of this study indicated that 78% show interest in using E-Tembang, while 66% like and are interested and 86% want to use it. However, it is undeniable that 23% of students do not like learning by using mobile telephones and prefer to study in the classroom. Basically, students will like to learn any subject that is attractive to them. By using E-Tembang students can learn together at home and share the knowledge of tembang macapat